Sources of Discreteness and Gradience in Island Effects - Chaves, Rui P. (Languages (Basel), 2022)
This paper provides an overview of categorical and gradient effects in islands, with a focus on English, and argues that most islands are gradient. In some cases, the island is circumvented by the construction type in which the extraction takes place, and there is growing evidence that the critical factor is pragmatic in nature, contrary to classic and categorical accounts of island effects that are favored in generative circles to this day. In other cases, the island effect is malleable and can weaken with increased exposure to the extraction pattern, a phenomenon traditionally referred to as ‘syntactic satiation’. However, it is not clear what satiation consists of. Some argue that it is nothing more than task adaptation (mere increased familiarity with the experimental paradigm, impacting difficult sentences more than easy ones), whereas others propose that it consists of a form of error-driven structure-dependent form of learning. The present paper discusses this controversy, and the broader adaptation debate, and argues that both task adaptation and grammatical adaptation are taking place during the processing of complex sentences, and that both frequency and attention are plausible factors to stimulate adaptation.